Economic Evaluation of Innovative Decisions Implementation as a Factor of Sustainable Economic and Industrial Development - ORLOV, Kirill P.; ORLOVA, Valeriya A. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2020)
In the last decade, there has been a trend of constant increase in the scale and share of organizational and managerial innovations in the total volume of innovative activity of enterprises. This is largely facilitated by the formation and development of creative management in the management of enterprises. However, today in the conceptual apparatus of creative management there are different approaches to the disclosure of its content, which creates certain difficulties, and often confusion, both in science and in practice. In solving theoretical and applied problems, we used a systematic approach, abstract-logical, graphical and analytical methods, economic-statistical and sociological methods, methods of comparison and analogy, complex economic analysis and expert assessments. Studies have shown the feasibility of further improvement of methods and tools of creative adaptive management, fundamentally different from previous analogues. The proposed methodological approach to the integrated assessment of efficiency will allow to evaluate the entire system of positive and negative effects of management activities, taking into account the anticipated consequences at the stage of development of enterprise development programs.